Gerald Brisch (ed). The Dodecanese: further travels among the insular Greeks. Selected writings of J. Theodore and Mabel V.A. Bent, 1885-1888 - Tzortzopoulou-Gregory, Lita (Journal of Greek Archaeology, 2016)
Brisch’s edition of a collection of selective travel writings of J. Theodore and Mabel V.A. Bent during their tour of the Dodecanese (1885–1888), is an interesting introduction to the couple’s rather eccentric and bemusing view of this part of the eastern Mediterranean. While the short preface by Marc Dubin and the introduction to the volume by Gerald Brisch provide the necessary background to the uninitiated reader of the importance of this genre of travelogues of the late 19th century, they are limited in their offering of a clear motive or logic behind the selection of the specific writings presented in this book. In other words, it is unclear as to how this selection of mostly already published articles came to be, and for what audience it is intended. While the editor refrains from interfering with the original writings by providing only a limited number of footnotes, the near absence of a detailed commentary makes it at times a tedious and rather repetitive read, providing hardly a historical or cultural context for the ordinary reader.